APPLICATION OF CLONAL SELECTION ALGORITHM FOR PID CONTROLLER SYNTHESIS OF MIMO SYSTEMS IN OIL AND GAS INDUSTRY - Shiryayeva, Olga; Samigulin , Timur (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
This paper presents the results of the Smart technologies application to the synthesis of MIMO-systems in oil and gas industry. In particular, there is considered a multidimensional multiply connected system for gas distillation process control through a distillation column with regulators configured on the basis of Smart-technologies – clonal selection algorithm (CLONALG) of an artificial immune system (AIS).